Degree of geometric tilting determines the activity of FeO₆ octahedra for water oxidation - Li, Haiyan (2020)
Fe oxides and (oxy)hydroxides are promising cost-effective catalysts for scalable water electrolysis. For an improvement in the understanding of the structural factors required by the most active Fe sites, the role of geometric tilting in determining the activity of the FeO6 octahedron for water oxidation was investigated. The catalytic performance of the FeO6 octahedron in a series of crystalline structures, i.e., perovskites AFeO3, spinel ZnFe2O4, and β-FeOOH, was found to be negatively correlated with their octahedral tilting degree. This correlation was rationalized through the Fe–O covalency, which is reflected by the O 2p band center as well as the charge-transfer energy obtained from ab initio calculations. Thus, it was disclosed that FeO6 octahedral tilting alters the activity for water oxidation through changing the covalency degree of Fe–O bonds.